Qori-khona Architecture of the 18th Century as the Naqshbandiya Museum - Odina Olimova; Azamat Rajabboyev (Indonesian Journal of Cultural and Community Development, 2025)
This study examines the architectural and cultural significance of the 18th-century Qori-khona in Kagan, currently functioning as the Naqshbandiya Museum, within the framework of Islamic educational architecture and Sufi traditions in Central Asia. The research addresses a critical gap in existing scholarship, which has predominantly focused on monumental madrasas and earlier historical periods while overlooking smaller-scale religious-educational structures and their contextual integration within the Naqshbandiya spiritual tradition. The investigation employed a qualitative methodology combining architectural analysis, field documentation, spatial surveys, and critical examination of historical and visual sources to evaluate the building's design principles, spatial organization, and adaptive reuse as a museum facility. Findings reveal that the Qori-khona exemplifies the Bukhara architectural school through its modest peshtaq, inward-oriented courtyard layout, minimalist ornamentation, and compact hujra configuration, all reflecting Naqshbandiya values of spiritual discipline, modesty, and contemplative concentration. The architectural composition demonstrates deliberate restraint in decoration and proportional harmony aligned with Sufi educational practices rather than syncretic or symbolic interpretations previously suggested in literature. The novelty of this research lies in establishing the Qori-khona as a coherent Islamic educational space rooted specifically in 18th-century Sufi architectural conventions, challenging generalized or chronologically imprecise characterizations. These findings contribute theoretical understanding of later-period Sufi architecture in Central Asia and provide practical implications for heritage conservation, demonstrating how adaptive reuse can maintain architectural integrity while extending the educational mission of religious monuments through contemporary museological frameworks.Keywords: Qori-khona architecture; Naqshbandiya Sufism; Bukhara architectural school; Islamic educational buildings; Central Asian heritage preservation; 18th-century religious monumentsHighlight :  The Qori-khona demonstrates coherent 18th-century Islamic educational architecture aligned with Naqshbandiya Sufi principles. Architectural features reflect intentional design emphasizing modesty, discipline, and inward spiritual focus through spatial organization. Museum adaptation successfully maintains architectural integrity while continuing the building's original educational purpose effectively.